PENGELOLAAN RIMBA LARANGAN ADAT KENEGERIAN RUMBIO PADA ZONA PEMANFAATAN - Ninik Indrayani; Hasim As'ari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Utilization zone is a zone that can be used for the benefit of Rumbio village community. This research is a study to analyze the management of the ban on the forest customary Kenegerian Rumbio in the utilization zone with the customary forests of ± 500 Ha.  Management of the rimba larangan adat Kenegerian Rumbio has several problems; 1) management carried out on the rimba larangan adat in the utilization zone does not improve the welfare of society; 2) Not maximised implementation of planning rimba larangan adat  Kenegerian Rumbio in the utilization zone; and 3) The number of visitors has not increased. In seeing the management rimba larangan adat  Kenegerian Rumbio at the utilization zone, researchers used the concept of management function theory by Henry Fayol in Solihin (2010) which started from planning, organizing, directing and controlling. The research methods used are qualitative research methods. The result of this research is the management rimba larangan adat Kenegerian Rumbio in the optimal utilization zone. This is seen from the research results that there are several sub indicators on the concept of management that have not yet met namely; 1) Setting goals; 2) formulating the current state; 3) Divide the components of activities needed to achieve the objectives; 4) quality; 5) time; 6) determining performance standards; 7) measuring performance standards; 8) Make repairs in case of deviation from the standard.  Unfulfilled sub indicators are caused by several factors; 1) budget factors; 2) human resources factors; 3) communication factors; 4) Factors of facilities and infrastructure; and 5) Factors of government support (incentives).Keywords: Management, Utilization Zone